Continuity Theory of Ageing and Leisure Participation among Elderly Attending Selected Health Clinics in Selangor - HS, Minhat; MA, Rahmah; S, Khadijah (IIUM Medical Journal Malaysia, 2013)
Introduction: Leisure participation in old age is often a continuation of their participation at younger age. This study aims to explore the association between current and former leisure participation of the elderly. Methods: A cross-sectional survey was conducted among 268 persons aged 60 years and above, purposively selected from eight health clinics in Selangor. Current leisure participation was measured using a validated Leisure Participation Questionnaire (LPQ), specific for Malaysian elderly. The LPQ consists of 25 activities, categorized into recreational (physical), cognitive, social and productive activity. Frequency of participation in each activity was measured on a 6-point scale. Leisure participation at younger age only involved their general participation in leisure. The most common daily leisure activities were having conversations while relaxing (78.7%) and watching television (74.6%), while the least were from playing golf (0.01±0.12) and performing musical instruments (0.04±0.36). More than half (64.9%) reported being actively involved in any leisure activity at younger age. Results: The study found there was a significant association between former and current leisure participation, especially for cognitive (t=-2.45, p=0.015), social (t=-2.68, p=0.008) and productive (t=-2.89, p=0.004) activities. However, only productive activity involvement was predicted by their leisure participation while younger (B=1.304, p=0.027). Conclusion: The findings suggest the importance of considering active intervention programmes at younger age to ensure better leisure participation of the elderly, especially in recreational physical activity.